Pengembangan Alat Permainan Edukatif Busy Book dalam Meningkatkan Aspek Perkembangan Anak - Suyadi, Suyadi; Zuniarsih, Zuniarsih (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
Technological advances today require parents and teachers to be more creative and innovative in learning with children, in this case for early childhood. One of them can be attempted by learning media or playing children. Many varieties of learning tools or media can be used by teachers to help the development of children, one of which is busy book. The Busy book in this study was named "My Little World". The type of research used is qualitative. The methods used are observation, interviews, and documentation. The results of this research are done using tools or medium of early childhood learning, which is made of patchwork and some sewing equipment that is no longer used. This Busy book contains a variety of simple play activities, including: puzzles, maze, finger puppets, attaching ropes, attaching buttons, matching colors and shapes, sorting patterns and so on. Busy book is a result of teacher creativity that can not be found in other institutions. Busy book was created to provide a more learning experience to the children who are already finished in playing activities with the teacher. The opportunity to play using busy book is designed with striking colors, giving its own appeal for the child. Another thing that characterizes the media is that, in one media play, the child can play and learn to develop various aspects of its development.